2000
DOI: 10.1103/physrevb.62.16612
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical study of the relative stability of structural phases in group-III nitrides at high pressures

Abstract: We present the results of a first-principles theoretical study of the relative stability of several structural phases of the group-III nitrides AlN, GaN, and InN that complements the picture of the behavior under pressure of these technologically important materials. Along with structures which have been previously considered in other theoretical studies of these materials ͑comprising those of the observed phases: wurtzite, zinc-blende, and rocksalt; and the d-␤-Sn, NiAs, and CsCl structures͒ we have also asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

35
76
4

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 204 publications
(115 citation statements)
references
References 63 publications
35
76
4
Order By: Relevance
“…As shown in Table 3, while our obtained the phase transition pressure value, showing quantitative deviation from the experimental value of 52.2 ± 3.0 [27] and theoretical values of 44.80 [2], 45.00 [5] and 40.00 [43], is comparable to that of other DFT within GGA and LDA calculation founded as 32.40 [3], 31.00 [6], and 33.7 [33], respectively.…”
Section: Structural Parameterssupporting
confidence: 73%
“…As shown in Table 3, while our obtained the phase transition pressure value, showing quantitative deviation from the experimental value of 52.2 ± 3.0 [27] and theoretical values of 44.80 [2], 45.00 [5] and 40.00 [43], is comparable to that of other DFT within GGA and LDA calculation founded as 32.40 [3], 31.00 [6], and 33.7 [33], respectively.…”
Section: Structural Parameterssupporting
confidence: 73%
“…By synchrotron energy-dispersive X-ray diffraction, Xia et al reported the first observation of rocksalt phase at an onset pressure of 37 GPa (Xia et al, 1993). Additional later studies confirmed that GaN with different forms all underwent the wurtzite to rocksalt transformation on compression, however, with large discrepancies in transition pressures (e.g., 42-54 GPa for experimental results (Halsall et al, 2004;Perlin et al, 1992;Ueno et al, 1994) and 37-55 GPa for some theoretical studies (AbuJafar et al, 2000;Cai & Chen, 2007;Mujica et al, 2003;Munoz & Kunc, 1991;Pandey et al, 1996;Serrano et al, 2000)). GaN can also be synthesized in the nanocrystalline form, either as nanowires or as quantum dots (Jorgensen et al, 2003;Liu et al, 2003;Zhou et al, 2005).…”
Section: Properties Structures and Applications Of Ganmentioning
confidence: 97%
“…The transformation from wurtzite to hexagonal for II-VI and III-IV compounds has already been studied. [9][10][11][12][13][14][15][16] In the above studies, treated compression conditions are basically hydrostatic (isotropic) with the exception of c=a compression 10,14) mentioned later. The hexagonal phase is treated as an intermediate or metastable phase between a wurtzite !…”
Section: )mentioning
confidence: 99%
“…10,11,14) As for wAlN and w-ZnO, they transform into hexagonal phases under hydrostatic compression. 11,12,14) The transformation of 17,18) and has been theoretically studied. 19,20) At first, we investigated w-BN as one of the candidates.…”
Section: )mentioning
confidence: 99%
See 1 more Smart Citation